Detection of genes providing salinity-tolerance in rice - doi: 10.4025/actascibiolsci.v36i1.15437 (Acta Scientiarum. Biological Sciences, 2013)
The present study aimed to identify salinity-tolerant genes in three cultivars (BRS-7 Taim, BRS Querência and BRS Atalanta) of Oryza sativa L. ssp. indica S. Kato and in three cultivars (BRS Bojurú, IAS 12-9 Formosa and Goyakuman) of Oryza sativa L. ssp. japonica S. Kato. Ten days after emergence seedlings were transferred to a greenhouse and placed in a 15L vessel with half strength Hoagland nutrient solution, which was changed every four days, under controlled temperature and humidity. Plants were harvested 56 days after transfer. DNA extraction was carried out by CTAB method and salinity-tolerant genes SOS and CK1 were identified by in silico research. Amplification of gene sequence was performed with in silico primers. Bands were detected by agar gel electrophoresis and visualized under ultraviolet light after staining with ethidium bromide. Gene SOS1 fragments were present in all cultivars, except in BRS Atalanta, whereas CK1 gene was present in all evaluated cultivars. Results show that salinity-tolerant genes under analysis were identified in the two sub-species.